Accounting treatment and taxable income. - Ng, Hui Fang. (2008)
Accounting standards and tax law had developed independently in ascertaining what “profit” is. Position of the courts in the UK and Singapore on the weightage of accounting evidence accorded in tax cases is assessed. A commentary follows on the feasibility of an alignment of accounting and taxable profits in Singapore.